Research note: jail staff views of inmate medical care and fear of being at risk - Lambert, Eric G. (Criminal justice studies, 2024)
Correctional staff are sometimes in fear of being injured on the job. Concerns about issues relating to inmate medical care could be related to feeling at risk on the job for staff. The current study explored how perceived inmate medical care issues were related to fear of being at risk on the job among staff at a large Southern US jail. The provided survey asked about staff about their concerns of being at risk and medical views dealing with if infectious diseases are handled correctly, if quality medical care was provided to inmates, if staff responded in a timely manner, if there was a high turnover of medical staff, and if inmate privacy rates put staff at risk. In a multivariate regression analysis, a view that inmate infectious diseases are handled correctly and quality medical care is provided were significantly related to lower levels fear of being in danger from the job, while the view that inmate medical privacy rights placed staff at risk had a positive effect. Views that staff respond quickly to inmate medical needs and that there is a high level of medical staff turnover both had nonsignificant effects on fear of being at risk at work.